2021
DOI: 10.1029/2021jg006318
|View full text |Cite
|
Sign up to set email alerts
|

Ice Cover Influences Redox Dynamics in Prairie Pothole Wetland Sediments

Abstract: The Prairie Pothole Region (PPR) of North America encompasses nearly 750,000 km 2 of the Upper Great Plains that straddle the United States and Canada. This region is composed of a heavily glaciated landscape densely populated by depressional wetlands connected hydrologically by groundwater with little surface water connectivity. Thus, wetland surface area varies greatly with annual precipitation patterns (Liu & Schwartz, 2011). These wetlands also exhibit a salinity gradient ranging from <800 to >60,000 µS/cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…75 Although our measurements captured only the icefree summer behavior of redox-active solutes, it is highly likely that they are inuenced by winter hydrodynamics. 74,76,77 Future studies will be paramount in linking winter hydrodynamics, mixing, and hydrology to biogeochemical cycling in order to determine the effect of decreasing ice cover on methane production within Arctic lake sediments. Previous studies have linked methane transport from active layers of permafrost thaw and ground water into near shore, shallow areas of Toolik Lake.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…75 Although our measurements captured only the icefree summer behavior of redox-active solutes, it is highly likely that they are inuenced by winter hydrodynamics. 74,76,77 Future studies will be paramount in linking winter hydrodynamics, mixing, and hydrology to biogeochemical cycling in order to determine the effect of decreasing ice cover on methane production within Arctic lake sediments. Previous studies have linked methane transport from active layers of permafrost thaw and ground water into near shore, shallow areas of Toolik Lake.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…McAdams et al. (2021) observed the migration of reduced sulfur species from several centimeters below the sediment‐water interface when no ice was present in shallow Prairie Pothole lakes to at or above the sediment‐water interface under the ice. Another study found a relationship between methane oxidation and P content among different lakes (Sawakuchi et al., 2021), which could also be a redox‐related relationship given that phosphate is released from sediments at higher rates under lowered redox states (Mortimer, 1942).…”
Section: Physical and Biogeochemical Dynamicsmentioning
confidence: 99%